CHARACTERISTICS OF MIDDLE UTERINE ARTERY AND FETAL UMBILICAL BLOOD FLOW IN PREGNANT MURRAH BUFFALO - SINGH, G; CHANDOLIA, R K; DUTT, R; SAINI, A; MALIK, R K (The Indian Journal of Animal Reproduction, 2022)
Six healthy Murrah buffalo were assessed for middle uterine artery and fetal umbilical blood flow at regularinterval from day 18 of gestation onward. Resistance index and pulsatility index of middle uterine artery wasinvariably similar (p>0.05) from day 30 of gestation onward. However, these indices exhibited a decreasing (p
Keywords: Color Doppler; Murrah buffalo; Middle uterine artery; Pregnant; Umbilicus